2010
DOI: 10.1177/1049732310385123
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Identity Negotiations Among Low-Income Women With Symptoms of Postpartum Depression

Abstract: In this study, we used a constructivist grounded theory approach to explore maternal identity negotiations among low-income ethnic minority mothers with postpartum depression (PPD) symptoms. Nineteen mothers were recruited from Women, Infant, and Children clinics located in two coastal cities in the United States to participate in in-depth interviews. Constant comparative analysis revealed that mothers experienced their PPD symptoms and poverty as evidence of maternal failure, but also drew on discourses of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 36 publications
5
54
0
Order By: Relevance
“…This fear is not unfounded, since some mothers may seek to construct a positive maternal identity by comparing themselves to others in similar circumstances, and judging their own parenting to be superior (Abrams and Curran, 2010). Several healthcare studies have demonstrated that women who have a problematic experience of early motherhood may experience shame and guilt due to a perceived failure to meet maternal ideals, and be less inclined to reach out for support from health care providers (Abrams et al, 2009;Foulkes, 2011 Fear of judgement was also evident in online forum interactions, with not all online experiences reported as positive, and causing some mothers to avoiding posting (describing themselves as or to consult offline sources.…”
Section: Fear Of Judgmentmentioning
confidence: 99%
“…This fear is not unfounded, since some mothers may seek to construct a positive maternal identity by comparing themselves to others in similar circumstances, and judging their own parenting to be superior (Abrams and Curran, 2010). Several healthcare studies have demonstrated that women who have a problematic experience of early motherhood may experience shame and guilt due to a perceived failure to meet maternal ideals, and be less inclined to reach out for support from health care providers (Abrams et al, 2009;Foulkes, 2011 Fear of judgement was also evident in online forum interactions, with not all online experiences reported as positive, and causing some mothers to avoiding posting (describing themselves as or to consult offline sources.…”
Section: Fear Of Judgmentmentioning
confidence: 99%
“…Moreover, there is strong evidence that in addition to benefiting mothers' wellbeing, these reforms would bolster children's emotional and social development and learninghelping families across the country rise out of poverty [13], parenting [26], appropriate counseling session and psychotherapy is crucial to increase their mental well-being [27], Awareness of any potential differences may help early childhood professionals who work with mothers with depression [19] Healing programs: the first thing to do is getting know the sign of maternal depression and how to deal with, Cognitive therapy, spiritual belief, associating their mind to the wellness, remembering the calm and confidence associated with health and happiness, contemplation, simple attitude of prayerfulness and a feeling of empathy, caring, and compassion for the entity in need, seemed to set the stage for healing [28] sharing [24], Treating maternal depression is crucial to improving parenting and getting children's development back on track for school and adult success, including escaping poverty. There is strong evidence that a variety of safe and effective tools exist for treating adults with depression, including pharmacotherapies, psychotherapies, behavioral therapies, and alternative medicines.…”
Section: Prevention and Healingmentioning
confidence: 99%
“…3 A woman's self-identity may be tied to a mother's self-defined failures to fulfill societal expectations. 12 Taking on this so-called bad mother identity, coupled with the stigma of mental illness, can inhibit reaching out for help. 13 As a result, women may be fearful of disclosing symptoms and concerns to health care practitioners.…”
Section: Stigma Intensive Mothering and Essentialismmentioning
confidence: 99%
“…5 The fear of society labeling a woman as a bad mother can lead to shame and avoidance in seeking treatment. 12 My experiences with postpartum depression showed me that I not only fully subscribed to intensive mothering norms, it subconsciously helped shape my depression and postpone my own treatment.…”
mentioning
confidence: 99%